التفسير المقاصدي للآيات الكونية دراسة تأصيلية تطبيقية مقاصد ذكر الأرض في القرآن نموذجا - عباسي إبراهيم (University of eloued جامعة الوادي, 2025)
يتناول هذا البحث موضوع التأصيل لمنهج التفسير المقاصدي للآيات الكونية، وتطبيقه على نموذج موضوعي هو ذكر الأرض في القرآن، في محاولة لربط التأصيل النظري بالتطبيق العملي الممنهج؛ ساعيا في تعزيز الحاجة إلى قراءة مقاصدية للقرآن الكريم بما يشتمل عليه من آيات، خاصة الكونية منها، في ظل الحاجة إلى توظيف المقاصد القرآنية في تفسير النصوص والاستفادة منها في معالجة قضايا الإنسان والكون والحياة. وقد انتظم البحث في ثلاثة مباحث كان المبحث الأول في مفهوم التفسير المقاصدي، ودرست في المبحث الثاني مفهوم الآيات الكونية، وكان المبحث الثالث وهو الدراسة التطبيقية في إبراز المقاصد من ذكر الأرضفي القرآن والكشف عنها عقدية منها وعمرانية وسلوكية وعامة؛ وقد خلص البحث إلى جملة من النتائج من أبرزها وضع تعريف للتفسير المقاصدي. وأن التفسير المقاصدي امتداد وتخصص لما سبقه من تفاسير معتمدة. إن الخوض في هذا الفن يحتاج إلى ملكات ذهنية ودوافع تحصيلية وضوابط علمية تعصم صاحبها من الخطأ والتقول على الله بما لم يقل. أن موضوع ذكر الأرض في القرآن الكريم تجاوز الوقوف عند التدبر والاعتبار إلى مقاصد أخرى هي الاستدلال والتكليف والاستخلاف والعمارة، وذلك واضح جلي في نموذج ""ذكر الأرض في القرآن في تحقيق التفاعل بين النص والكون للاستفادة من ذلك في الواقع المعيش. This research addresses the topic of establishing the methodology of the teleological interpretation of cosmic verses, and applying it to a thematic model, namely the mention of the Earth in the Qur'an. This research attempts to link theoretical foundations with systematic practical application, seeking to reinforce the need for a teleological reading of the Holy Qur'an, including its verses, especially cosmic ones, in light of the need to employ Qur'anic objectives in interpreting texts and benefiting from them in addressing issues related to humanity, the universe, and life. The research is organized into three sections: the first section examines the meaning of teleological interpretation; the second section examines the concept of cosmic verses; and the third section, an applied study, highlights the objectives of the mention of the Earth in the Qur'an and explores them in terms of doctrine, urbanism, behavior, and generality. The research concludes with a few results, the most prominent of which is the establishment of a specific definition of teleological interpretation, and that teleological interpretation is an extension and specialization of the approved interpretations that preceded it. Delving into this art requires intellectual abilities, academic motivation, and scientific controls that protect the practitioner from error and attributing to God what He did not say. The mention of the Earth in the Holy Quran transcends contemplation and reflection, encompassing other purposes, including reasoning, assignment, succession, and development. This is clearly evident in the model of The Mention of the Earth in the Quran, which explores the interaction between the text and the universe to benefit from this in real-life situations.
ماستر تفسير
Keywords: المقاصد; الآيات الكونية; الأرض; interpretation; objectives; cosmic verses